Numerical simulation of stress amplification induced by crack interaction in human femur bone - Noor Alia, Md Zain
This research is about numerical simulation using computational method which study on stress amplification induced by crack interaction in human femur bone. Crack in human femur bone usually occur because of large load or stress applied on it. Usually, the fracture takes longer time to heal itself. The crack interaction is still not well understood due to bone complexity. Thus, brittle fracture behaviour of bone may be underestimated and inaccurate. This study aims in investigating the geometrical effect of double co-planar edge cracks on stress intensity factor (K) in femur bone. Other than that, this research also focus in the amplification effect on fracture behaviour of double co-planar edge cracks, where numerical model is developed using computational method. The concept of fracture mechanics and numerical approaches to solve interacting cracks problems using linear elastic fracture mechanics (LEFM) theory is used. So, it is important to study what is the parameter that can minimize the crack propagation to prevent complete failure. This study has shown that the crack interaction limit (CIL) and crack unification limit (CUL) exist in the model developed. In future development of this research, several improvements will be made such as varying the load, applying thickness on the model and also use different theory or method in calculating the stress intensity factor (K).